Low-carbon 3D printing concrete prepared from ultra-low cement large admixture gelling system
By introducing modified quartz sand, microsilicon powder, fly ash and other admixtures into 3D printed concrete, and using liquid crystal polymers and allyl methacrylate, the compressive strength of ultra-low cement content concrete is solved. and insufficient volume stability have achieved the dual goals of high strength and low carbon environmental protection.
Patent Information
- Application Number
- CN202411881515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing ultra-low cement content 3D printed concrete is insufficient in terms of compressive strength and volume stability, making it difficult to meet the construction needs of complex structures.
Adopt ultra-low cement large admixture gelling system, by introducing modified quartz sand, microsilicon powder, fly ash and kaolin blends, and improves by liquid crystal polymer wrapping and allyl methacrylate admixtures. The interface bonding force between aggregate and cement slurry is optimized to improve the mechanical properties of concrete.
It significantly improves the compressive strength and volume stability of 3D printed concrete, reduces the amount of cement, achieves the goal of low-carbon environmental protection, and improves the overall performance and durability of the material.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of building materials, and more specifically, to an ultra-low cement and large admixture cementitious system for preparing low-carbon 3D printed concrete. Background Art
[0002] With the rapid development of the construction industry, 3D printing concrete, as an emerging construction technology, is gradually showing its great potential in the construction of complex structures, improvement of construction efficiency and material saving. Among them, the ultra-low cement and large admixture cementitious system, as an important component of 3D printing concrete, aims to achieve low-carbon production of concrete by reducing the amount of cement and increasing the proportion of admixtures such as industrial waste, while maintaining or improving its mechanical properties and printing performance to meet the needs of future green buildings.
[0003] In the current 3D printing concrete technology, researchers have explored a variety of ultra-low cement content cementitious systems to reduce carbon emissions and improve resource utilization efficiency. These systems usually include industrial waste such as slag, fly ash, and silica fume as admixtures, and achieve a significant reduction in cement usage by optimizing the mix ratio and the use of activators. However, these systems still face some challenges in practical applications, such as insufficient development of compressive strength and poor volume stability of concrete after hardening.
[0004] How to significantly improve the strength and volume stability of 3D printed concrete while ensuring ultra-low cement usage to meet the needs of complex structure 3D printing is an urgent problem that needs to be solved. Summary of the invention
[0005] In order to improve the compressive strength and volume stability of 3D printed concrete, the present application provides an ultra-low cement and large admixture cementitious system for preparing low-carbon 3D printed concrete.
[0006] The present application provides an ultra-low cement and large admixture cementitious system for preparing low-carbon 3D printed concrete, using the following technical solution: An ultra-low cement and large admixture cementitious system is used to prepare low-carbon 3D printing concrete, comprising the following raw materials in parts by weight: 30-50 parts of silicate cement, 15-20 parts of kaolin, 20-30 parts of modified quartz sand, 0.5-2 parts of water reducer, 0.1-0.3 parts of hydroxypropyl methylcellulose ether, 10-15 parts of microsilica powder, 1-3 parts of admixture, 8-12 parts of fly ash, 18-24 parts of allyl methacrylate and 50-60 parts of water. The modified quartz sand is obtained by encapsulating and modifying the liquid crystal polymer.
[0007] By adopting the above technical solution, the reduction in cement dosage will lead to a reduction in the gelling substances produced by the hydration reaction, thereby affecting the connection between the aggregate and the matrix material, and the appearance of weak connection areas leads to a decrease in the overall strength of the concrete. Therefore, the liquid crystal polymer solution is used to wrap the aggregate. The liquid crystal polymer has a unique molecular structure and performance, which can improve the interface bonding between the aggregate and the cement paste to a certain extent. By wrapping the aggregate with the liquid crystal polymer solution, a thin film can be formed on the surface of the aggregate. This film can enhance the bonding force between the aggregate and the cement paste, reduce the formation of weak connection areas, and make the quartz sand better dispersed in the concrete. Further, the allyl methacrylate in the raw material reacts with the liquid crystal polymer on the surface of the aggregate to improve the compatibility between the aggregate and the matrix material, further strengthen the interface bonding force of the concrete, and thus improve the compressive strength of the concrete. Microsilica fume and fly ash have a certain alkali absorption capacity. They can react with the alkali in the concrete, thereby reducing the alkali concentration in the pore solution and reducing the occurrence of alkali-silica reaction. Kaolin has good volcanic ash effect and filling effect, which can improve the pore structure characteristics of concrete and significantly improve the mechanical properties of concrete.
[0008] By introducing a large amount of mineral admixtures such as kaolin, modified quartz sand, microsilica powder and fly ash that are enhanced by encapsulation and modification of liquid crystal polymers, the amount of silicate cement used is effectively reduced, thereby reducing carbon emissions while utilizing the volcanic ash effect and filling effect of these admixtures to significantly improve the compressive strength of concrete. In addition, the addition of hydroxypropyl methylcellulose ether and water reducer optimizes the fluidity and workability of the concrete mixture, promotes the uniform distribution and dense stacking of cement hydration products, and further enhances the volume stability and durability of concrete. The addition of allyl methacrylate enhances the bonding force between materials through chemical action, and at the same time helps to improve the overall performance of concrete. In summary, this application achieves the dual goals of low-carbon environmental protection and high-strength concrete preparation by optimizing the material ratio and introducing high-performance admixtures and admixtures.
[0009] Optionally, the preparation of modified quartz sand comprises the following steps: Take 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione and dissolve them in toluene to form a uniform monomer solution, continue to add 2,2-dimethoxy-2-phenylethylbenzophenone and stir thoroughly, add raw material quartz sand and soak for 2-3 hours, heat to 60-70°C and irradiate with ultraviolet light for 2-4 minutes, filter and dry to obtain modified quartz sand.
[0010] By adopting the above technical solution, 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione are used as liquid crystal polymer precursors, heated in toluene solvent, and 2,2-dimethoxy-2-phenylacetophenone is added as a photoinitiator. The reaction is irradiated with ultraviolet light, and a polymer chain with special liquid crystal properties is formed through a photo-initiated free radical polymerization reaction, which is attached to the surface of quartz sand to form a uniform liquid crystal polymer film. The lubricating effect of the liquid crystal polymer film helps to improve the fluidity and workability of the concrete mixture, making the concrete more uniform and smooth during mixing, transportation and pouring, while improving the rigidity and hardness of the aggregate, improving the bonding strength between the aggregate and the cement paste, and improving the overall strength of the concrete.
[0011] Optionally, during the preparation of the modified quartz sand, each raw material is added according to the following weight parts: 30-40 parts of 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, 8-11 parts of 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione, 2-3 parts of 2,2-dimethoxy-2-phenylacetophenone, 55-62 parts of toluene, and 20-30 parts of raw material quartz sand.
[0012] By adopting the above technical scheme and controlling the above raw materials, especially the amount of each monomer added, better encapsulation of quartz sand is ultimately achieved, modified quartz sand with excellent performance is prepared, and the compressive strength and volume stability of concrete are improved.
[0013] Optionally, the particle size of the raw quartz sand is between 0.2-3 mm.
[0014] By adopting the above technical solution, the particle size of quartz sand affects the final modification effect. Controlling the particle size of quartz sand within this range is conducive to the full adsorption and penetration of liquid crystal polymer solution, helping to form a more uniform and denser wrapping layer and improving the modification effect. At the same time, a smaller particle size helps to fill the tiny pores in concrete, reduce the porosity, and thus improve the compressive strength of concrete.
[0015] Optionally, the immersion temperature during the immersion process is 40-50°C.
[0016] By adopting the above technical solution, the appropriate temperature helps to further promote the dissolution and mixing of the monomers, ensure the uniformity of the solution, and at the same time helps to promote the adsorption and penetration of liquid crystal polymers on the surface of quartz sand, forming a uniform and dense coating layer, thereby improving the strength of the modified quartz sand.
[0017] Optionally, the additive is lithium carbonate.
[0018] By adopting the above technical scheme, the active silicon oxide component in the raw material can easily react with the alkali in the cement to form an alkali silicate gel, which has strong water absorption and further expands after absorbing water, causing expansion stress inside the concrete, resulting in concrete cracking. The added lithium salt and phosphate can effectively inhibit the generation of alkali silicate gel, and can react with the alkali in the concrete to form stable compounds, thereby reducing the alkali concentration in the pore solution, reducing the occurrence of alkali silicate reaction, and improving the volume stability of the concrete.
[0019] Optionally, the water reducer is a polycarboxylic acid water reducer.
[0020] By adopting the above technical solution, the water-cement ratio of concrete can be further reduced, the density and strength of concrete can be improved, and it has good compatibility with components such as silicate cement, kaolin, modified quartz sand, etc. in the system, which helps to form a uniform and stable concrete slurry.
[0021] Optionally, prepared by the following method: (1) After weighing the raw materials, the modified quartz sand and allyl methacrylate are mixed and stirred once to obtain a primary mixture; (2) adding silicate cement, kaolin, microsilica fume, admixture, fly ash and hydroxymethyl cellulose ether to the primary mixture and stirring for a second time to obtain a secondary mixture; (3) Add equal amounts of a water reducing agent and water to the secondary mixture twice and stir to obtain 3D printed concrete.
[0022] In summary, this application has the following beneficial effects: 1. This application significantly reduces the amount of Portland cement by introducing a large amount of mineral admixtures such as kaolin, modified quartz sand, microsilica powder and fly ash. This mix design not only reduces carbon emissions in the cement production process, but also makes full use of industrial waste, achieving efficient resource utilization and circular economy. At the same time, these admixtures improve the pore structure of concrete through their volcanic ash effect and filling effect, further improving the mechanical properties of concrete.
[0023] 2. The modified quartz sand in this application is wrapped by the liquid crystal polymer solution, which enhances the bonding force between the aggregate and the cement paste, reduces the formation of weak connection areas, and thus improves the compressive strength of the concrete. In addition, the addition of allyl methacrylate further enhances the bonding force between the materials and optimizes the interface bonding of the concrete.
[0024] 3. The addition of hydroxypropyl methylcellulose ether and water reducing agent in the present application optimizes the fluidity and workability of the concrete mixture, promotes the uniform distribution and dense stacking of cement hydration products, and further enhances the volume stability and durability of the concrete. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0027] Portland cement was purchased from Lingshou County Qianfu Mineral Products Processing Plant, with a strength grade of 32.5; fly ash with a specific surface area of 300-500m 2 / kg, loss on ignition is not more than 2%; kaolin was purchased from Lingshou County Ruojia Mineral Products Co., Ltd., with a sieve residue of 5%, a moisture content of ≤2.2%, and a mesh size of 400 mesh; quartz sand was purchased from Lingshou County Xiaoshitou Mineral Products Co., Ltd., with a silicon dioxide content of 80%; microsilica powder was purchased from Shijiazhuang Baijiang Mineral Products Co., Ltd., with a silicon dioxide content of 93.02%.
[0028] Preparation Example
[0029] Preparation Example 1 A modified quartz sand, the preparation of which comprises the following steps: Take 35kg of 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 10kg of 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione and dissolve them in 62kg of toluene to form a uniform monomer solution, continue to add 3kg of 2,2-dimethoxy-2-phenylacetophenone and stir thoroughly, add 25kg of quartz sand, heat at 50°C and soak for 3h, heat to 70°C and irradiate with ultraviolet light for 3min to obtain modified quartz sand, wherein the particle size of the quartz sand is 0.15-3mm.
[0030] Preparation Example 2 A modified quartz sand, the preparation of which comprises the following steps: Take 40kg of 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 8kg of 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione and dissolve them in 55kg of toluene to form a uniform monomer solution, continue to add 2.5kg of 2,2-dimethoxy-2-phenylacetophenone and stir thoroughly, add 20kg of quartz sand, heat at 40°C and soak for 2h, heat to 60°C and irradiate with ultraviolet light for 4min to obtain modified quartz sand, wherein the particle size of the quartz sand is 0.15-3mm.
[0031] Preparation Example 3 A modified quartz sand, the preparation of which comprises the following steps: Take 30kg of 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 11kg of 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione and dissolve them in 58kg of toluene to form a uniform monomer solution, continue to add 2kg of 2,2-dimethoxy-2-phenylacetophenone and stir thoroughly, add 30kg of quartz sand, heat at 45°C and soak for 2.5h, heat to 65°C and irradiate with ultraviolet light for 2min to obtain modified quartz sand, wherein the particle size of the quartz sand is 0.15-3mm.
[0032] Preparation Example 4 A modified quartz sand, which is different from Preparation Example 1 in that the quartz sand added in this Preparation Example has a particle size of 3.15-6 mm.
[0033] Preparation Example 5 A modified quartz sand, which is different from Preparation Example 1 in that the quartz sand added in this Preparation Example has a particle size of 0.1-0.2 mm.
[0034] Preparation Example 6 A modified quartz sand, which is different from Preparation Example 1 in that the impregnation process in this Preparation Example is carried out at room temperature.
[0035] Preparation Example 7 A modified quartz sand, which is different from Preparation Example 1 in that the immersion temperature during the immersion process in this Preparation Example is 60°C.
[0036] Example
[0037] Example 1
[0038] A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system, and the preparation comprises the following steps: (1) After weighing all the raw materials, 25 kg of modified quartz sand and 21 kg of allyl methacrylate were mixed and stirred once to obtain a primary mixture; (2) adding 40 kg of Portland cement, 15 kg of kaolin, 15 kg of microsilica powder, 2 kg of lithium carbonate (admixture), 12 kg of fly ash and 0.2 kg of hydroxymethyl cellulose ether to the primary mixture and performing secondary stirring to obtain a secondary mixture; (3) After mixing 1 kg of water reducer and 60 kg of water, add the secondary mixture in equal amounts twice and stir to obtain 3D printed concrete. The water reducer is a DH-4005 polycarboxylic acid high-performance water reducer, and the modified quartz sand is prepared in Preparation Example 1.
[0039] Example 2
[0040] A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system, and the preparation comprises the following steps: (1) After weighing the raw materials, 30 kg of modified quartz sand and 18 kg of allyl methacrylate were mixed and stirred once to obtain a primary mixture; (2) adding 30 kg of Portland cement, 18 kg of kaolin, 10 kg of microsilica powder, 1 kg of lithium carbonate (admixture), 10 kg of fly ash and 0.3 kg of hydroxymethyl cellulose ether to the primary mixture and stirring for a second time to obtain a secondary mixture; (3) After mixing 2 kg of water reducer and 50 kg of water, add the secondary mixture in equal amounts twice and stir to obtain 3D printed concrete. The water reducer is a DH-4005 polycarboxylic acid high-performance water reducer, and the modified quartz sand is prepared in Preparation Example 2.
[0041] Example 3
[0042] A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system, and the preparation comprises the following steps: (1) After weighing all the raw materials, 20 kg of modified quartz sand and 24 kg of allyl methacrylate were mixed and stirred once to obtain a primary mixture; (2) adding 50 kg of Portland cement, 20 kg of kaolin, 12.5 kg of microsilica powder, 3 kg of lithium carbonate (admixture), 8 kg of fly ash and 0.1 kg of hydroxymethyl cellulose ether to the primary mixture for secondary stirring to obtain a secondary mixture; (3) After mixing 0.5 kg of water reducer and 55 kg of water, add the secondary mixture in equal amounts twice and stir to obtain 3D printed concrete. The water reducer is a DH-4005 polycarboxylic acid high-performance water reducer, and the modified quartz sand is prepared in Preparation Example 3.
[0043] Example 4
[0044] A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system. The difference from Example 1 is that the modified quartz sand used in this example is prepared in Preparation Example 4.
[0045] Example 5
[0046] A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system. The difference from Example 1 is that the modified quartz sand used in this example is prepared in Preparation Example 5.
[0047] Example 6
[0048] A low-carbon 3D printed concrete is prepared by an ultra-low cement and large admixture cementitious system. The difference from Example 1 is that the modified quartz sand used in this example is prepared in Preparation Example 6.
[0049] Example 7
[0050] A low-carbon 3D printed concrete is prepared by an ultra-low cement and large admixture cementitious system. The difference from Example 1 is that the modified quartz sand used in this example is prepared in Preparation Example 7.
[0051] Comparative Example
[0052] Comparative Example 1 A low-carbon 3D printing concrete is prepared by an ultra-low cement and large admixture cementitious system, which is different from Example 1 in that unmodified quartz sand is added in this comparative example.
[0053] Comparative Example 2 An ultra-low cement and large admixture cementitious system is used to prepare low-carbon 3D printing concrete, which is different from Example 1 in that allyl methacrylate is not added in this comparative example.
[0054] Comparative Example 3 The low-carbon 3D printing concrete was prepared by using an ultra-low cement and large admixture cementitious system. The difference from Example 1 is that kaolin, microsilica powder and fly ash were not added in this comparative example.
[0055] Performance testing Detection Methods
[0056] Compressive strength: A 100mm×100mm×100mm cubic specimen was used with a loading rate of 1MPa / s. The compressive strength of the specimen at room temperature was tested in accordance with GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete"; Volume stability: refer to the shrinkage test in GBJ82 "Test method for long-term performance and durability of ordinary concrete" to test the volume stability. Take the 100×100×515mm prism specimen as the standard specimen for the experiment, and calculate the shrinkage rate by the average value of three times.
[0057] Table 1 Test results
[0058] Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the various test data of Examples 1-3 are better than those of Comparative Example 1, indicating that the modified quartz sand prepared in the present application improves the performance of concrete by increasing the bonding strength between quartz sand and other components in the slurry, and on the other hand, the modification of quartz sand by liquid crystal polymer further improves the rigidity of the aggregate itself, thereby further improving the compressive strength of the concrete.
[0059] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the test data of Examples 1-3 are better than those of Comparative Example 2, and the addition of allyl methacrylate can further improve the connection tightness between materials and thus improve the compressive strength of concrete.
[0060] It can be seen from Examples 1-3 and Comparative Example 3 and Table 1 that the various test data of Examples 1-3 are better than those of Comparative Example 3, indicating that the improvement in performance in the present application partly depends on the synergistic effect of kaolin, microsilica powder and fly ash with other raw materials in the present application, which promotes the uniform distribution and dense stacking of cement hydration products, thereby improving the compressive strength and volume stability of concrete.
[0061] It can be seen from Examples 1-5 and Table 1 that the various test data of Examples 1-3 are better than those of Examples 4-5, indicating that the particle size of quartz sand affects the modification effect. Quartz sand with a suitable particle size not only plays a skeleton support role in the slurry, but also quartz sand in this particle size range is conducive to the full adsorption and penetration of the liquid crystal polymer solution, thereby improving the modification effect and thus improving the strength of the concrete.
[0062] Combining Example 1 with Examples 6-7 and Table 1, it can be seen that the various test data of Example 1 are better than those of Examples 6-7, indicating that the immersion temperature is controlled between 40-50°C when modifying quartz sand. The appropriate temperature helps to promote the adsorption of the solution on the surface of the quartz sand, which is beneficial to the subsequent polymerization modification process. At the same time, the liquid crystal polymer can maintain its unique liquid crystal phase structure within a specific temperature range. At a temperature of 40-50°C, the liquid crystal polymer can maintain good liquid crystal phase stability, which helps it to be arranged in an orderly manner on the surface of the quartz sand to form a uniform adsorption layer.
[0063] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A low-carbon 3D printing concrete prepared by an ultra-low cement and large admixture cementitious system, characterized in that: The composition comprises the following raw materials in parts by weight: 30-50 parts of silicate cement, 15-20 parts of kaolin, 20-30 parts of modified quartz sand, 0.5-2 parts of water reducer, 0.1-0.3 parts of hydroxypropyl methylcellulose ether, 10-15 parts of microsilica powder, 1-3 parts of admixture, 8-12 parts of fly ash, 18-24 parts of allyl methacrylate and 50-60 parts of water. The modified quartz sand is obtained by encapsulating and modifying the liquid crystal polymer.
2. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 1 is characterized in that: The modified quartz sand preparation comprises the following steps: Take 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene and 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione and dissolve them in toluene to form a uniform monomer solution, continue to add 2,2-dimethoxy-2-phenylethylbenzophenone and stir thoroughly, add raw material quartz sand and soak for 2-3 hours, heat to 60-70°C and irradiate with ultraviolet light for 2-4 minutes, filter and dry to obtain modified quartz sand.
3. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 2 is characterized in that: During the preparation of the modified quartz sand, each raw material is added according to the following weight parts: 30-40 parts of 1,4-bis[4-(6-acryloyloxyhexyloxy)benzoyloxy]-2-methylbenzene, 8-11 parts of 4,5-dithiodiethylene-1,3-dithiocyclopentene-2-thione, 2-3 parts of 2,2-dimethoxy-2-phenylacetophenone, 55-62 parts of toluene, and 20-30 parts of raw material quartz sand.
4. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 2, characterized in that: The particle size of the raw quartz sand is between 0.2 and 3 mm.
5. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 2, characterized in that: The immersion temperature during the immersion process is 40-50°C.
6. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 1, characterized in that: The additive is lithium carbonate.
7. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
8. The method for preparing low-carbon 3D printing concrete using an ultra-low cement large admixture cementitious system according to claim 1, characterized in that: Prepared by the following method: (1) After weighing the raw materials, the modified quartz sand and allyl methacrylate are mixed and stirred once to obtain a primary mixture; (2) adding silicate cement, kaolin, microsilica fume, admixture, fly ash and hydroxymethyl cellulose ether to the primary mixture and stirring for a second time to obtain a secondary mixture; (3) Add equal amounts of a water reducing agent and water to the secondary mixture twice and stir to obtain 3D printed concrete.
Citation Information
Patent Citations
Composition for reinforcing binding power and use thereof
CN104610880A
High-performance concrete dry mixture and use method thereof
CN109678413A
Low-alkali cement concrete acid-resistant pile and preparation method thereof
CN115477524A
Reactive powder concrete and preparation process thereof
CN116143463A
Dry cementitious mortar, useful as an adhesive or coating composition comprises cement, a redispersible polymer powder and zinc oxide, zinc hydroxide or zinc hydroxide carbonate.
DE10109841A1